Sistema de Comando Remoto por Voz para un Móvil - Velasco Peña, Hugo Fernando; Escandón Moscoso, Miguel; Rodríguez Garavito, César H. (Ingeniería, 2001)
This document presents a study of some of the main technologies available for speech recognition and wireless communications. Also the implementation of a mobile system is presented, this mobile is able to respond to the user´s voice, by using of efficient methods for the movement control. The speech recognition system of voice commands obtained after evaluation of several options, was achieved through the use of integrated circuit HM2007, which is implemented in a neuronal network, for vocal commands identification. The commands are codified and transmitted later by infrared way. The information arrives at the mobile and is processed by the control digital systems, which govern of direct way his behavior. The speech recognition system is portable and independent of mobile, which it commands of remote form to, so that it could be adapted to other tasks, that imply the speech control .